PENGUKURAN KUALITAS SISTEM INFORMASI INVENTARIS ASET UNIVERSITAS MUHAMMADIYAH BENGKULU MENGGUNAKAN METODE MCCALL - Khairullah Khairullah; Bambang Soedijono; Hanif Al Fatta (Universitas Janabadra, 2017)
Measurement of Inventory Information System Asset University of Muhammadiyah Bengkulu conducted to measure the quality of asset inventory information system application of Muhammadiyah University of Bengkulu based on user perception using McCall method. The measurement process of asset inventory information system of Muhammadiyah University of Bengkulu is done by several stages of measurement using several quality factors on the McCall method namely; correctness, reliability, efficiency, integrity and usability to know how far the quality and level of user utilization of the current asset inventory information system. The measurement process using the McCall method involves 18 respondents, where the results of this application measurement get the percentage of total quality of 68.4% and included in the good category. However, further development is needed to improve user utilization and the quality of the inventory asset information system itself better. Keywords : Pengukuran, Kualitas, McCall, Inventaris Aset